On Aesthetic Judgments and Contemplative Perception in the Critique of the Power of Judgment - Laiho, Hemmo (Con-Textos Kantianos. International Journal of Philosophy, 2020)
The paper argues that much of Kant’s largely formalistic account of aesthetic appreciation stands on the idea that the judger is able to engage with the object of her judgment purely sensibly and hence non-conceptually or non-cognitively. This is to say that the judger must be able to ground her judgment on the immediate sensory affection by the object (which makes her judgment an aesthetic judgment of sense) or on the object’s sensible form (which makes her judgment an aesthetic judgment of taste). The paper also argues that these two purely sensible grounds, accessible in the aesthetic examination of objects, underlie the feeling involved in such judgments. In broader terms, the paper outlines how Kant’s account of aesthetic judgment suggests what might be called a contemplative model of perception.